Apigenin delivery composite material containing flaxseed gum oligosaccharide as well as preparation method and application of apigenin delivery composite material
By coating flaxseed gum oligosaccharides on the surface of zein nanoparticles, apigenin delivery composite materials are formed, which solves the problems of poor water solubility and low bioavailability of apigenin, and an efficient and biocompatible delivery system is achieved, which significantly improves stability and antioxidant activity.
Patent Information
- Application Number
- CN202510016050.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-11
AI Technical Summary
The poor water solubility and low bioavailability of apigenin lead to its limited application and requires the development of efficient delivery systems to overcome these limitations.
Apigenin delivery composite material containing flaxseed gum oligosaccharides was used to form zein nanoparticles by anti-solvent precipitation method, and the surface of the nanoparticles was coated with flaxseed gum oligosaccharides to enhance the stability and biocompatibility of apigenin.
It significantly improves the stability of apigenin in various environments, enhances the antioxidant activity in vitro, provides an efficient and biocompatible delivery system for hydrophobic biologically active substances, and improves bioaccessibility and bioavailability.
Smart Images

Figure CN119792235A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomaterials, and in particular to an apigenin delivery composite material containing flaxseed gum oligosaccharide, and a preparation method and application thereof. Background Art
[0002] Apigenin (Ap) is a natural flavonoid widely found in fruits, vegetables and oil crops, and has multiple health benefits, such as antioxidant, antithrombotic, anti-inflammatory, antispasmodic, hypoglycemic, anticancer and myocardial ischemic injury protection. These multifaceted biological activities make Ap a promising functional ingredient in the food and pharmaceutical industries. However, its application is severely limited by its poor water solubility (less than 2.16 μg / mL) and low bioavailability, and the development of efficient delivery systems is needed to overcome these limitations.
[0003] To address these challenges, various nano-delivery systems have been tailored, including APISL nanoparticles, W / O / W emulsions, and protein-based nanoparticles. Among them, protein-based delivery vehicles have unique advantages in biodegradability, digestibility, and cost-effectiveness. Zein, a hydrophobic protein from corn, shows great potential in encapsulating Ap due to its unique structure with more than 50% hydrophobic amino acid residues. However, zein nanoparticles still face stability issues, such as hydrophobic aggregation, which affects their delivery effect.
[0004] Therefore, there is an urgent need to develop new nanodelivery systems for Ap delivery to provide efficient and biocompatible delivery systems for hydrophobic bioactive substances and improve delivery stability, antioxidant activity and other properties.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The purpose of the present invention is to provide an apigenin delivery composite material containing flaxseed gum oligosaccharides, and a preparation method and application thereof, aiming to enhance the stability of Ap in various environments, thereby enhancing the in vitro antioxidant activity, and providing an efficient and biocompatible delivery system for hydrophobic bioactive substances.
[0007] The present invention is achieved in that:
[0008] In a first aspect, the present invention provides an apigenin delivery composite material containing flaxseed gum oligosaccharides, comprising nanoparticles formed by zein, wherein the interior of the nanoparticles contains apigenin, and the surface of the nanoparticles is coated with flaxseed gum oligosaccharides.
[0009] In an optional embodiment, the mass ratio of the nanoparticles formed by zein to apigenin is (15-25):1, and the mass ratio of the nanoparticles to flaxseed gum oligosaccharides is (0.5-4):1;
[0010] Preferably, the average molecular weight of flaxseed gum oligosaccharides is 1000-1800Da;
[0011] Preferably, the apigenin delivery composite material containing flaxseed gum oligosaccharides is solid particles or an aqueous solution;
[0012] Preferably, the particle size of the nanoparticles is less than 150 nm.
[0013] In a second aspect, the present invention provides a method for preparing the apigenin delivery composite material containing flaxseed gum oligosaccharides according to the aforementioned embodiment, wherein nanoparticles are formed by an antisolvent precipitation method, comprising:
[0014] The alcohol solution of zein is mixed with apigenin to obtain a mixed alcohol solution;
[0015] The flaxseed gum oligosaccharide aqueous solution and the mixed alcohol solution are mixed, and the alcohol solvent is removed.
[0016] In an optional embodiment, during the preparation process, the mass ratio of zein to apigenin is controlled to be (15-25):1, and the mass ratio of zein to flaxseed gum oligosaccharide is controlled to be (0.5-4):1.
[0017] In an optional embodiment, the preparation process of the mixed alcohol solution includes: mixing zein and an alcohol solvent to make the concentration of zein 8 mg / mL-12 mg / mL, then mixing with apigenin, adjusting the pH value to 3.8-4.2, and stirring for 2h-7h.
[0018] In an optional embodiment, the alcohol solvent is an ethanol solution with a volume fraction of 75%-85%;
[0019] And / or, the pH value is adjusted to 3.8-4.2 using a hydrochloric acid solution with a concentration of 0.05-0.20 mol / L.
[0020] In an optional embodiment, the preparation process of the flaxseed gum oligosaccharide aqueous solution includes: mixing flaxseed gum oligosaccharide and water, and adjusting the pH value to 3.8-4.2;
[0021] And / or, in the aqueous solution of flaxseed gum oligosaccharide, the concentration of flaxseed gum oligosaccharide is 0.625 mg / mL-5 mg / mL.
[0022] In an optional embodiment, the mixed alcohol solution is added to the flaxseed gum oligosaccharide aqueous solution, mixed and stirred for 0.5h-3h, the alcohol solvent is evaporated to remove, and then mixed with an aqueous solution with a pH value of 3.8-4.2.
[0023] In an optional embodiment, the method further comprises: after mixing with an aqueous solution having a pH value of 3.8-4.2, freeze-drying to obtain a solid granular material.
[0024] In a third aspect, the present invention provides the use of an apigenin delivery composite material containing flaxseed gum oligosaccharides according to any of the aforementioned embodiments or an apigenin delivery composite material containing flaxseed gum oligosaccharides prepared by any of the preparation methods according to the aforementioned embodiments in the preparation of apigenin products.
[0025] The present invention has the following beneficial effects: the present invention utilizes zein and apigenin (Ap) to form nanoparticles, and coats flaxseed gum oligosaccharides (FGOS) on the surface of the nanoparticles, thereby enhancing the stability of Ap under various pH, heat, light, ionic strength, storage, redispersion and simulated gastrointestinal environments, thereby enhancing the in vitro antioxidant activity, improving the bioaccessibility and bioavailability, and providing an efficient and biocompatible delivery system for hydrophobic bioactive substances. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0027] Figure 1 Figure 1 is a performance test diagram of different mass ratios of FG or FGOS to Zein@Ap; A and B represent the particle size, PDI and zeta potential of FG / Zein@Ap at different mass ratios; C and D represent the particle size, PDI and zeta potential of FGOS / Zein@Ap at different mass ratios; E represents the particle size distribution of Zein@Ap, FG / Zein@Ap and FGOS / Zein@Ap nanoparticles at a mass ratio of 2:1; F represents the image of Zein@Ap, FG / Zein@Ap and FGOS / Zein@Ap nanoparticles; GH represents the EE and LC of FG / Zein@Ap and FGOS / Zein@Ap nanoparticles at different mass ratios, and different letters indicate statistically significant differences (P<0.05);
[0028] Figure 2Figure 2 is the stability evaluation result of Zein@Ap, FG / Zein@Ap and FGOS / Zein@Ap nanoparticles; AC represents pH stability: particle size, zeta potential and appearance; DF represents thermal stability: particle size, Ap retention rate and thermal degradation kinetics; G represents photostability; HI represents ionic strength stability: particle size and zeta potential; JL represents storage stability: particle size and Ap retention rate at 25°C, and appearance of freshly prepared Zein@Ap, FG / Zein@Ap and FGOS / Zein@Ap after 30 days of storage; MN represents redispersion stability: particle size and particle size distribution before and after freeze-drying and redispersion; different letters represent statistically significant differences (P<0.05);
[0029] Figure 3 are the test results of Ap's release performance, bioaccessibility, cytotoxicity and other performances; A represents the release curve; BC represents the average particle size and TEM image of free Ap, Zein@Ap, FG / Zein@Ap and FGOS / Zein@Ap nanoparticles in the simulated gastrointestinal digestion process; D represents the bioaccessibility of Ap in Zein@Ap, FG / Zein@Ap and FGOS / Zein@Ap nanoparticles; EH represents the cytotoxicity of the digested samples after incubation in Caco-2 cells for 4 hours; IK represents the cell uptake, transmembrane transport and bioavailability of Ap in the digested samples after Caco-2 cells were cultured for 4 hours; different letters represent statistically significant differences (P<0.05);
[0030] Figure 4 The three-dimensional structure and the principle diagram of action; A represents the three-dimensional structure of Ap, zein, FG and FGOS; B represents the predicted binding energy, binding mode and interaction mechanism of zein and Ap, zein and FG / FGOS;
[0031] Figure 5 Characterization of the structure and morphology of Zein@Ap, FG / Zein@Ap and FGOS / Zein@Ap nanoparticles. (A) FTIR spectra; (BC) XRD spectra; (DF) TEM images;
[0032] Figure 6 Antioxidant activities of Zein@Ap, FG / Zein@Ap and FGOS / Zein@Ap nanoparticles. (A) DPPH free radical scavenging activity; (B) ABTS free radical scavenging activity. Different letters indicate statistically significant differences (P<0.05). DETAILED DESCRIPTION
[0033] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0034] Polysaccharides are often introduced as stabilizers to improve the colloidal stability of protein nanoparticles. Flaxseed gum (FG) is a natural polysaccharide extracted from flaxseed with good water solubility and biocompatibility. However, FG has high viscosity and low charge density, which limits its efficiency as a stabilizer. Recent studies have found that small molecule oligosaccharides not only have the potential to stabilize protein nanoparticles, but also effectively enhance their bioactivity. The currently reported flaxseed gum oligosaccharides (FGOS) have an average molecular weight of 1000-1800 kDa and are functionally superior to FG, including better water solubility, lower viscosity, higher carboxyl content and stronger bioactivity. In addition, FGOS has been shown to modulate the composition of the intestinal microbiota and improve the intestinal barrier function. Despite these excellent properties, it is not expected whether FGOS can provide better performance than FG in zein nanoparticles for hydrophobic biodelivery such as Ap.
[0035] The present invention uses the antisolvent precipitation method to develop FGOS-coated zein nanoparticles (FGOS / Zein@Ap) for Ap delivery, and compares its effects with those of FG / Zein@Ap and Zein@Ap systems, and systematically optimizes the encapsulation efficiency and drug loading. The structural and morphological characteristics of the nanoparticles were analyzed using Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD) and transmission electron microscopy (TEM). In addition, their stability, antioxidant activity, bioaccessibility, cellular uptake and bioavailability were also evaluated.
[0036] The embodiment of the present invention provides a method for preparing an apigenin delivery composite material containing flaxseed gum oligosaccharides, wherein nanoparticles are formed by an antisolvent precipitation method, and the steps are as follows:
[0037] S1. Preparation of Zein-Apigenin Mixed Alcohol Solution
[0038] The alcohol solution of zein was mixed with apigenin to obtain a mixed alcohol solution, during which a small number of nanoparticles were formed.
[0039] In some embodiments, during the preparation process, the mass ratio of zein to apigenin is controlled to be (15-25):1, such as 15:1, 18:1, 20:1, 23:1, 25:1, etc. By optimizing the mass ratio of zein to apigenin, the delivery effect of apigenin can be further improved and its stability can be improved.
[0040] Furthermore, the preparation process of the mixed alcohol solution includes: mixing zein and an alcohol solvent to make the concentration of zein 8mg / mL-12mg / mL, then mixing with apigenin, adjusting the pH value to 3.8-4.2, stirring for 2h-7h, and ensuring complete dissolution to obtain a mixed alcohol solution. By adjusting the pH value to about 4, zein is made positively charged (the isoelectric point of zein is 5.5-6.5), which is convenient for assembly with negatively charged FGOS through electrostatic adsorption.
[0041] Specifically, by adjusting the amount of zein and alcohol solvent, the concentration of zein can be 8 mg / mL, 9 mg / mL, 10 mg / mL, 11 mg / mL, 12 mg / mL, etc.; the stirring time can be 2h, 3h, 4h, 5h, 6h, 7h, etc.
[0042] In some embodiments, the alcohol solvent used may be an ethanol solution with a volume fraction of 75%-85%, specifically an ethanol aqueous solution, and the volume fraction of ethanol may be 75%, 78%, 80%, 82%, 85%, etc.
[0043] In some embodiments, the pH value can be adjusted to 3.8-4.2 using a hydrochloric acid solution having a concentration of 0.05-0.20 mol / L. The use of a hydrochloric acid solution to adjust the pH value has readily available raw materials and is convenient to operate. The concentration of the hydrochloric acid solution can be 0.05 mol / L, 0.08 mol / L, 0.10 mol / L, 0.13 mol / L, 0.15 mol / L, 0.18 mol / L, 0.20 mol / L, etc.
[0044] S2, FGOS coating
[0045] The linseed gum oligosaccharide aqueous solution and the mixed alcohol solution are mixed, the alcohol solvent is removed, and the anti-solvent precipitation method is used to form nanoparticles, so that the linseed gum oligosaccharide is coated on the surface of zein. The outer layer of the zein particle is hydrophilic and the inner layer is hydrophobic, and apigenin enters the hydrophobic interior, and the surface of the zein particle is coated with linseed gum oligosaccharide.
[0046] In some embodiments, during the preparation process, the mass ratio of zein to linseed gum oligosaccharide is (0.5-4):1, such as 0.5:1, 1.0:1, 1.5:1, 2.0:1, 2.5:1, 3.0:1, 3.5:1, 4.0:1, etc. The amount of linseed gum oligosaccharide used is preferably within the above range, which can significantly improve the stability of Ap delivery, improve its antioxidant activity, bioaccessibility and other properties. The average molecular weight of the linseed gum oligosaccharide used is 1000-1800Da.
[0047] Furthermore, the preparation process of the flaxseed gum oligosaccharide aqueous solution includes: mixing flaxseed gum oligosaccharide and water, and adjusting the pH value to 3.8-4.2; in the flaxseed gum oligosaccharide aqueous solution, the concentration of flaxseed gum oligosaccharide is 0.625-5 mg / mL (such as 0.625 mg / mL, 0.833 mg / mL, 1.25 mg / mL, 2.5 mg / mL, 5 mg / mL, etc.). By adjusting the concentration of flaxseed gum oligosaccharide, the amount of water is more appropriate, providing a solvent environment for self-assembly.
[0048] Further, the mixed alcohol solution is added to the linseed gum oligosaccharide aqueous solution, mixed and stirred for 0.5h-3h (such as 0.5h, 1.0h, 2.0h, 3.0h, etc.), the alcohol solvent is evaporated to remove, and then mixed with an aqueous solution with a pH value of 3.8-4.2, and the volume of the added aqueous solution can be equal to the volume of the removed alcohol solvent. The alcohol solvent can be removed by rotary evaporation, but is not limited thereto.
[0049] In some embodiments, the method further comprises: after mixing with an aqueous solution having a pH value of 3.8-4.2, freeze drying is performed to obtain a solid granular material. Freeze drying can be selectively performed according to the requirements of the product form. If a solid granular material is required, freeze drying is performed, and if a solution product is required, freeze drying is not required.
[0050] The embodiment of the present invention also provides an apigenin delivery composite material containing flaxseed gum oligosaccharides, including nanoparticles formed by zein, the interior of the nanoparticles contains apigenin, and the surface of the nanoparticles is coated with flaxseed gum oligosaccharides. The preparation process can refer to the preparation method provided in the embodiment of the present invention.
[0051] It should be noted that apigenin is a bioactive compound with significant health benefits, but its application is limited by poor solubility, stability and bioavailability. The present invention provides zein nanoparticles (FGOS / Zein@Ap) coated with flaxseed oligosaccharides (FGOS) for Ap delivery. Test results such as dynamic light scattering, FT-IR, XRD and TEM show that compared with FG / Zein@Ap, FGOS / Zein@Ap has smaller size, higher zeta potential, encapsulation efficiency (~71.70%) and loading capacity (~7.66%) and other properties. Compared with FG / Zein@Ap, Zein@Ap and free Ap, it enhances the stability of Ap under various pH, heat, light, ionic strength, storage, redispersion and simulated gastrointestinal environments, thereby enhancing the in vitro antioxidant activity and improving bioaccessibility and bioavailability. Molecular docking revealed that the stronger interaction between FGOS and zein was mainly mediated by hydrogen bonds and van der Waals forces.
[0052] In some embodiments, the mass ratio of nanoparticles formed by zein to apigenin is (15-25):1, and the mass ratio of nanoparticles to flaxseed gum oligosaccharides is (0.5-4):1. By regulating the mass ratio of each raw material, the stability of Ap in various pH, heat, light, ionic strength, storage, redispersion and simulated gastrointestinal environments can be further enhanced, the in vitro antioxidant activity can be enhanced, and the bioaccessibility and bioavailability can be improved.
[0053] Furthermore, the apigenin delivery composite material containing flaxseed gum oligosaccharides can be solid particles or aqueous solution, and the particle size of the contained nanoparticles is less than 150 nm.
[0054] The apigenin delivery composite material containing flaxseed gum oligosaccharides provided in the embodiment of the present invention can be further prepared into apigenin products, which can significantly improve the delivery effect of apigenin and better exert the efficacy of apigenin.
[0055] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0056] Description of the materials used in the following examples and comparative examples: Zein was obtained from Solarbio Company (Beijing, China). Linseed gum FG was provided by Xinjiang Lishide Biotechnology Co., Ltd. Apigenin Ap was obtained from McLean (Shanghai, China). Pepsin, trypsin, and bile salts were purchased from Sigma-Aldrich (St Louis, MO, USA). CCK-8 was purchased from Shanghai Tianyu Biotechnology Co., Ltd., China. 1,1-Diphenyl-2-pyridine hydrazine radical (DPPH), 2,2'-nitrogenated nitrogen-(3-ethylbenzothiazole-6-sulfonate) (ABTS) were purchased from Shanghai Aladdin Industrial Co., Ltd., China. FGOS was prepared according to the method reported in the literature, with specific reference to: International Journal of Biological Macromolecules, 2020, 153, 1107-1116.
[0057] Example 1
[0058] This embodiment provides a method for preparing an apigenin delivery composite material containing flaxseed gum oligosaccharides, and the steps are as follows:
[0059] (1) 0.2 g of zein was dissolved in 80% ethanol solution at a concentration of 10 mg / mL. Ap was then added at a mass ratio of 20:1 (the mass ratio of Ap:zein was 1:20), and stirred at 600 rpm (pH 4.0, adjusted with 0.1 M HCl) for 4 hours to ensure complete dissolution to obtain a mixed alcohol solution.
[0060] (2) Dissolve the FGOS solution in ultrapure water at pH 4.0 (FGOS concentration is 0.625 mg / mL) at a speed of 600 rpm. Add the resulting mixed alcohol solution to the FGOS solution (control the mass ratio of zein to FGOS to be 4:1) and mix at 600 rpm for 1 hour. Evaporate the ethanol in the suspension and add an equal volume of aqueous solution (pH 4.0).
[0061] Note: The pH 4.0 aqueous solution was prepared as follows: 0.1 M HCl solution was added to deionized water to adjust the pH to 4.0.
[0062] Example 2
[0063] The only difference from Example 1 is that the FGOS concentration in the FGOS aqueous solution is configured to be 0.833 mg / mL, the mass ratio of zein to the added FGOS is controlled to be 3:1, the particle size of the nanoparticles is increased from 107.1±0.62 nm at 4:1 to 125.7±1.95 nm at 3:1, the encapsulation efficiency is increased from 40.1±3.55% at 4:1 to 54.2±2.56% at 3:1, and the loading rate is increased from 4.66±0.41% at 4:1 to 6.03±0.28% at 3:1.
[0064] Example 3
[0065] The only difference from Example 1 is that the FGOS concentration in the FGOS aqueous solution is configured to be 1.25 mg / mL, the mass ratio of zein to the added FGOS is controlled to be 2:1, the particle size of the nanoparticles is 132.1±0.51 nm, the encapsulation efficiency is 71.7±2.41%, and the loading rate is 7.66±0.25%.
[0066] Example 4
[0067] The only difference from Example 1 is that the FGOS concentration in the FGOS aqueous solution is configured to be 2.5 mg / mL, the mass ratio of zein to the added FGOS is controlled to be 1:1, the particle size of the nanoparticles is 209.2±1.82 nm, the encapsulation efficiency is 57.6±4.41%, and the loading rate is 6.24±0.47%.
[0068] Example 5
[0069] The only difference from Example 1 is that the FGOS concentration in the FGOS aqueous solution is configured to be 5.0 mg / mL, the mass ratio of zein to the added FGOS is controlled to be 0.5:1 (i.e., 1:2), the particle size of the nanoparticles is 380.9±16.23 nm, the encapsulation efficiency is 33.6±5.64%, and the loading rate is 2.38±0.41%.
[0070] Comparative Examples 1-5
[0071] The only difference from Examples 1-5 is that FGOS is replaced by an equal amount of FG, and the obtained product is expressed as FG / Zein@Ap. That is, in Comparative Example 1, FGOS in Example 1 is replaced by an equal amount of FG; in Comparative Example 2, FGOS in Example 2 is replaced by an equal amount of FG, and the ratio is changed from 4:1 to 1:2. The particle size of the nanoparticles is 242.23±0.64 to 826.50±34.23nm, and the loading amount and encapsulation efficiency reach the maximum of 60.43±2.66% and 3.61±0.15% at a ratio of 2:1.
[0072] Comparative Example 6
[0073] This comparative example provides a blank control, step (1) is the same as Example 3, and step (2) is as follows:
[0074] The mixed alcohol solution was gradually dripped into the aqueous solution at pH 4.0 and mixed at 600 rpm for 1 h. The concentration of zein in the obtained suspension was 2 mg / mL and the concentration of Ap was 0-100 μg / mL. Subsequently, the ethanol in the suspension was evaporated and an equal volume of aqueous solution (pH 4.0) was added. The obtained product was denoted as Zein@Ap.
[0075] That is, the main difference between step (2) of comparative example 2 and step (2) of example 1 is that FGOS is not added.
[0076] Test Example 1
[0077] The test examples and comparative examples provide the properties of the materials, and the test methods are as follows:
[0078] (1) Measurement of particle size and zeta potential:
[0079] The hydrated particle size and zeta potential of the nanoparticles were measured using a nano-zs90 nanosizer (Malvern Instruments Ltd., UK).
[0080] (2) Determination of encapsulation efficiency (EE) and loading capacity (LC):
[0081] The sample was diluted with ethanol and then subjected to ultrasonic destruction for 10 minutes to fully release the Ap in the nanoparticles. After that, it was centrifuged at 10,000 rpm for 20 minutes. The resulting solution was filtered with a 0.22 μm membrane. The EE and LC of Ap were then calculated using the following formula:
[0082]
[0083] (3)FT-IR analysis
[0084] The FT-IR wavenumber range of Zein@Ap, FG / Zein@Ap, and FGOS / Zein@Ap was recorded on a Bruker VECTOR22 spectrometer (Germany) in the range of 4000 to 400 cm -1 .
[0085] (4)XRD
[0086] The XRD spectra of the nanoparticles were analyzed using a MiniFlex 600 diffractometer at a voltage of 40 kV and an angle of 5° to 60° in the 2θ range.
[0087] (5)TEM
[0088] The nanoparticles were diluted with deionized water and then transferred to the surface of the carbon-coated support copper grid and then air-dried. The corresponding characterization was performed on a transmission electron microscope JEOL (JEM-2100F, Japan) at an accelerating voltage of 80 kV.
[0089] (6) Stability evaluation
[0090] pH stability: The effect of pH on the nanoparticles was evaluated. The pH of the samples was adjusted to 2.0, 4.0, 6.0, 8.0, 10.0, and 12.0 with 0.1 M HCl or NaOH solution and maintained for 24 h, and then the size and zeta potential of the samples were measured.
[0091] Thermal stability: All samples (5 ml) were heated at temperatures of 50, 65 and 80° C. for 30 minutes and then cooled to 25° C. Subsequently, the particle size and residual amount of Ap were measured and calculated.
[0092] Thermal degradation kinetics: The thermal degradation kinetics of Ap in nanoparticle dispersions were analyzed according to the reported protocol (Food Chemistry, 2024, 430, 137110). The samples were incubated at 80°C for 2, 4, 6, 8 and 10 h. The remaining Ap content was then measured according to the procedure of (2) encapsulation efficiency (EE) and loading capacity (LC). Using the data obtained, the degradation rate constant (k) and half-life (t 1 / 2 ).
[0093]
[0094] Where C0 and C represent the Ap concentration and initial concentration at time t(h).
[0095] Photodegradation kinetics: The photostability of Ap in nanoparticles was evaluated (ACS Applied materials & interfaces, 2019, 41, 38103-38115). The samples were exposed to UV radiation (0.35 W / m 2 ). After 2, 4, 6, 8 and 10 h of irradiation, the remaining Ap content was measured as described in (2) Encapsulation efficiency (EE) and loading capacity (LC). Using this data, the degradation rate constant (k) and half-life (t 1 / 2 ).
[0096] Ionic strength stability: An equal volume of the nanoparticle solution was mixed with a NaCl solution so that the final NaCl concentration of each dispersion was 0, 10, 20, 30, 40, and 50 mmol / L. The mixture was stirred at 500 rpm for 15 min and then allowed to stand at room temperature for 24 h. Afterwards, the particle size and zeta potential were measured.
[0097] Storage stability: Samples (20 mL) were stored at 25°C for 30 days to evaluate long-term stability. During storage, including evaluations at 0, 5, 10, 15, 20, 25 and 30 days, the particle size and the amount of Ap remaining in the dispersion were measured.
[0098] Redispersion behavior: The redispersibility of freeze-dried nanoparticle samples in water was evaluated (Food Chemistry, 2022, 391, 133224). Briefly, 20 mg of freeze-dried powder was added to 10 mL of deionized water, stirred at 600 rpm for 2 h, and then the particle size was measured.
[0099] (7) Evaluation of antioxidant activity
[0100] DPPH radical scavenging activity: The diluted sample (0.2 mL, equal amount of Ap) was mixed with 1 mL of DPPH (0.2 mM, 70% ethanol solution) and reacted in the dark for 30 minutes. The absorbance of the above solution was measured at 517 nm. The DPPH radical scavenging rate was calculated as follows:
[0101]
[0102] In formula 5, A and A0 are the absorbance of the sample and blank group, respectively.
[0103] ABTS free radical scavenging activity: ABTS reaction solution was prepared according to previous work (Food Chemistry, 2024, 456, 140021). Then 75 μL of samples of different concentrations were added to 1.0 mL of ABTS solution, stored in a dark environment for 6 min, and the absorbance of the solution at 734 nm was recorded. The ABTS scavenging rate was calculated as follows:
[0104]
[0105] In formula 6, A and A0 are the absorbance of the sample and blank group, respectively.
[0106] (8) In vitro simulation of gastrointestinal digestion and bioaccessibility
[0107] In vitro simulated gastrointestinal digestion: Initially, 20 mL of the nanoparticle sample was mixed with 20 mL of pepsin-simulated gastric fluid (SGF) containing pH 2.0 (Food Chemistry, 2024, 438, 137963). The mixture was kept at 37°C and shaken continuously at 150 rpm for 120 min. 1 mL was removed every 30 min and an equal volume of fresh SGF was added to maintain the total volume. After the gastric digestion period, 20 mL of the solution was collected for further analysis. Subsequently, the collected solution was mixed with 20 mL of simulated intestinal fluid (SIF) containing pancreatic enzymes and bile salts at pH 7.4. The mixture was then shaken continuously at 150 rpm for 120 min at 37°C. Similar to the gastric phase, 1 mL of the mixture was removed every 30 min and an equal volume of fresh SIF was added. At each time point, the nanoparticle size and free Ap release rate were determined after centrifugation. In order to examine the structural changes of the nanoparticles, the digestive fluids of the gastric and intestinal phases were analyzed using TEM.
[0108] Bioaccessibility: After simulated gastrointestinal digestion, the digested samples were centrifuged at 1000 rpm for 0.5 h, and the supernatant was first collected, ethanol was added, and then vortexed. The nanoparticles were then disrupted by ultrasonic treatment, and the mixture was centrifuged once. After centrifugation, the supernatant was collected. Finally, the Ap content in the filtered supernatant was quantified.
[0109]
[0110] Wherein, B1 and B0 are the Ap contents before and after digestion, respectively.
[0111] (9) Cellular transport and bioavailability
[0112] Cytotoxicity: Human colorectal cancer Caco-2 cells were cultured at 5×10 4 The cells were seeded into a 96-well plate at a density of 100 cells and incubated overnight. The digested samples were diluted so that the Ap concentration was in the range of 0 to 75 μg / mL. Subsequently, the cells were incubated for 4 hours, after which the medium was discarded and fresh medium was added to wash the cells. Finally, the CCK-8 solution was added to the cells and incubated for another 30 minutes, after which the absorbance of the solution was measured at 450 nm. Cell viability was calculated using the following formula:
[0113]
[0114] Where A S , A c , A b are the absorbance values of the sample wells, control wells and blank wells, respectively.
[0115] Transmembrane transport in Caco-2 cells: To assess cellular transport of digested samples, 1 × 10 5Caco-2 cells / well were plated and cultured overnight in a transwell system. DMEM medium was changed every 2 days for the first week and then every day thereafter (days 11-25). Transepithelial electrical resistance (TEER) values reached 500Ω·cm 2 , cell monolayers were used for cellular transport. In the apical (AP) to basolateral (BL) transport experiment, 1.5 mL of blank HBSS was added to the BL chamber and 0.5 mL of digestion solution sample was added to the AP chamber. The basolateral solution was collected at 4 different time points (1, 2, 3, and 4 h) and the transport content of AP was analyzed.
[0116] After completing the above steps, pre-cooled HBSS was added to stop the transport process, and the cells were washed three times with PBS. The cells were then lysed on ice for 30 minutes using a lysis buffer consisting of PBS and 10% ethanol. The lysate was ultrasonically destroyed and centrifuged at 10,000 rpm for 2 minutes. The resulting supernatant was collected for measuring the transported Ap concentration. The transport efficiency and cellular uptake rate of Ap were calculated as follows:
[0117]
[0118] Where M BL is the transport amount on the BL side (μg), M Initial is the amount of sample added on the AP side (μg).
[0119]
[0120] Where M uptake is the total content of Ap in the cell, M digestion is the total content of Ap after digestion.
[0121] Bioavailability: The bioavailability of free Ap and Ap in different samples was calculated based on the bioaccessibility and cellular uptake data (Food Chemistry 2021, 360, 130152). The calculation formula is as follows:
[0122] Bioavailability (%) = F B ×F A ×100% (11);
[0123] In the formula, F B is the bioaccessibility of the sample, F A is the cellular uptake rate of the sample.
[0124] The test results are as follows:
[0125] (1) Effects of FG and FGOS on cell size and potential
[0126] FG / Zein@Ap and FGOS / Zein@Ap nanoparticles with different mass ratios were prepared to explore the effects of FG and FGOS. Figure 1 Figure A shows that the initial hydrodynamic diameter of zein@Ap nanoparticles is 102.63±0.55nm. After the addition of FG, the particle size increases due to the distribution of large FG molecules on the positively charged surface of zein nanoparticles. When the mass ratio of Zein@Ap to FG is 4:1 to 1:2, the particle sizes are 242.23±0.64 to 826.50±34.23nm, respectively. It is worth noting that at higher FG content ratios (1:1 and 1:2), the particle size exceeds 500nm and is not suitable for delivery systems. In terms of zeta potential, all FG / Zein@Ap nanoparticles with different mass ratios reversed the potential of Zein@Ap ( Figure 1 (B). The FG / Zein@Ap nanoparticles with a ratio of 2:1 obtained a zeta potential of -29.30 ± 1.64 mV, indicating a stable structure and moderate size.
[0127] In contrast, at the same mass ratio, the particle size of FGOS / Zein@Ap nanoparticles is smaller than that of FG / Zein@Ap( Figure 1 C). The mass ratio of Zein@Ap to FGOS was 4:1 to 1:2, and the particle size ranged from 107.11±0.62 to 380.91±16.23nm. This difference was attributed to the smaller molecular weight of FGOS, which resulted in a tighter binding to the surface of zein and a more compact spatial structure. For zeta potential, FGOS / Zein@Ap nanoparticles showed a similar trend to that of FG / Zein@Ap nanoparticles ( Figure 1 D), but at a mass ratio of 2:1, due to the large number of carboxyl groups in FGOS, its negative potential (-43.85±3.31mV) is significantly higher than that of FG / Zein@Ap.
[0128] To strengthen the findings for the 2:1 mass ratio, the intensity distribution curves provided further insights. Figure 1 As shown in Figure E, both FG / Zein@Ap and FGOS / Zein@Ap exhibited narrow, sharp, and distinct peaks similar to those of Zein@Ap, indicating a uniform size distribution after coating with the FG or FGOS layer. FGOS / Zein@Ap maintained a size comparable to that of Zein@Ap, indicating a compact assembly relative to FG. All nanoparticles exhibited a clear Tyndall effect ( Figure 1 F), confirming successful formation under this optimized condition.
[0129] (2) EE and LC of Ap in FG / Zein@Ap and FGOS / Zein@Ap nanoparticles
[0130] High EE and LC are key parameters for nanoparticle delivery systems as they directly affect the bioactive effects. The EE and LC of Ap in FG / Zein@Ap and FGOS / Zein@Ap nanoparticles were determined at different ratios of zein to FG or FGOS. Figure 1 As shown in Figure GH. In the mass ratio range of 4:1 to 1:2, both EE and LC first increased, reached a maximum at a mass ratio of 2:1, and then decreased. At this ratio, the EE of Ap in FGOS / Zein@Ap nanoparticles reached 71.70±2.41%, which was significantly higher than the 60.43±2.66% of FG / Zein@Ap nanoparticles. In addition, the LC of FGOS / Zein@Ap was 7.66±0.25%, exceeding the 3.61±0.15% of FG / Zein@Ap. FGOS / Zein@Ap nanoparticles showed better performance, which may be due to the smaller molecular structure of FGOS after binding to zein, which reduced flocculation and precipitation during the formation of nanoparticles.
[0131] (3) Structural and morphological characterization
[0132] FT-IR:
[0133] like Figure 5 The difference between FG and FGOS in zein nanoparticles was analyzed by FT-IR characterization. The spectrum of zein nanoparticles is at 3319 cm -1 and 2960cm -1 Characteristic peaks are shown at 1658cm, representing OH stretching and alkyl CH stretching vibrations. -1 The peak at 1537 cm-1 and 1448 cm-1 corresponds to the C=O stretching vibration of the amide I band, while -1 The peak at 1655 cm-1 belongs to the amide II band, which is related to NH bending and stretching vibrations. -1 、1350cm -1 、1177cm -1 and 1030cm -1 The characteristic peaks of (C=O and C=C stretching vibrations, and CH bending vibrations of aromatic rings) disappeared, while the peak of zein at 3319 cm -1 The characteristic peak shifted to 3307cm -1 , indicating that hydrogen bonding promotes the inclusion of Ap in zein.
[0134] The characteristic peaks of FG and FGOS are at 3415 cm -1 and 3392cm -1 corresponds to OH stretching vibration, while 2925cm -1 and 2933cm-1 The position corresponds to CH stretching vibration. 1074cm -1 and 1070cm -1 The peaks reflect the stretching of CO in the pyranose ring. FG shows a peak at 1649 cm-1, which is related to the stretching vibration of the deprotonated carboxyl group. FGOS shows a peak at 1726 cm-1 -1 and 1654cm -1 (stretching vibration of esterified and non-esterified carboxyl groups of C=O) and 1413 cm -1 (asymmetric stretching vibration of C-OH and non-esterified carboxyl groups). The abundant free carboxyl groups lead to a peak at 1600 cm -1 and 1413cm -1 After the formation of FG / Zein@Ap and FGOS / Zein@Ap nanoparticles, the OH peak of Zein@Ap shifted from 3307cm in FG / Zein@Ap to -1 becomes 3394cm -1 , 3319cm in FGOS / Zein@Ap -1 , confirming the formation of hydrogen bonds between FG or FGOS and zein.
[0135] XRD:
[0136] The crystal structures of FG / Zein@Ap and FGOS / Zein@Ap nanoparticles were studied. Figure 5 As shown in Figure BC, the XRD spectrum of Ap shows obvious sharp peaks due to its crystalline nature, while the XRD spectra of zein, FG and FGOS show broad hill-like peaks, indicating their amorphous nature. The characteristic peaks of zein in FG / Zein@Ap and FGOS / Zein@Ap are all shifted to the right, indicating that there is an interaction between FG / FGOS and zein. In addition, the XRD spectra of all nanoparticles do not show crystalline peaks corresponding to Ap, indicating that Ap is encapsulated in the nanoparticles in an amorphous state. Amorphous structures usually have higher water solubility than crystalline forms, which may increase the bioavailability of Ap in FG / Zein@Ap and FGOS / Zein@Ap. Sharp diffraction peaks appear at 32.7° and 45.4°, which are characteristic of sodium chloride and may be caused by the acid-base neutralization step during the preparation of nanoparticles.
[0137] TEM:
[0138] The obtained nanoparticles were further characterized by TEM. Figure 5DF). Zein@Ap nanoparticles showed obvious agglomeration, which may be due to their high hydrophobicity in aqueous environment, resulting in adhesion and flocculation. FGOS / Zein@Ap nanoparticles had smaller particle size, uniform distribution, and improved stability and dispersibility. Although FG enhanced the dispersibility of FG / Zein@Ap nanoparticles, its size was larger than that of FGOS / Zein@Ap. FGOS prevented aggregation through a combination of steric repulsion and electrostatic repulsion, thus providing better stability.
[0139] (4) Stability
[0140] pH Stability:
[0141] The effect of pH on FG / Zein@Ap and FGOS / Zein@Ap was investigated. Figure 2 AC). At pH 2.0, Zein@Ap nanoparticles maintained a stable size of 108.4 ± 3.61 nm due to the stability of zein under acidic conditions. FG / Zein@Ap increased in size (428.13 ± 12.61 nm) due to a decrease in surface charge (-9.10 ± 0.17 mV). FGOS / Zein@Ap was smaller in size, 280.03 ± 11.88 nm. Near the isoelectric point of zein (pH 4.0-6.0), Zein@Ap increased dramatically with precipitation because the reduction in surface charge favored aggregation. In contrast, FG / Zein@Ap and FGOS / Zein@Ap remained stable near the isoelectric point, probably due to the coating of anionic polysaccharides, which prevented aggregation. In the pH range of 6.0-12.0, FG / Zein@Ap and FGOS / Zein@Ap maintained stable zeta potential and size. The zeta potential of FG / Zein@Ap ranged from -22.32±0.56mV to -28.8±0.76mV, and the size ranged from 227.83±3.95nm to 294.80±45.98nm; FGOS / Zein@Ap varied from -24.16±1.12mV to -32.63±0.81mV, and the size varied from 121.96±4.22nm to 172.56±7.83nm, indicating that electrostatic repulsion inhibited aggregation. Overall, FG and FGOS significantly improved the pH stability of the nanoparticles in the pH 2.0-12.0 range, with FGOS having better pH stability.
[0142] Thermal stability:
[0143] The stability of the nanoparticles at different temperatures was evaluated ( Figure 2DE in the middle). The particle size of FGOS / Zein@Ap did not change significantly. As the ambient temperature increased from 50℃ to 80℃, the particle size of Zein@Ap and FG / Zein@Ap nanoparticles increased. Higher temperatures may expose more hydrophobic amino acids in zein, increase hydrophobic attraction and overcome electrostatic repulsion, leading to nanoparticle aggregation and instability. At 50℃, the retention rate of Ap was: FGOS / Zein@Ap (98.38%) > FG / Zein@Ap (93.35%) > Zein@Ap (81.23%) > Ap (79.30%). At 65℃, the retention rate was: FGOS / Zein@Ap (97.89%) > FG / Zein@Ap (88.68%) > Zein@Ap (80.18%) > Ap (69.82%). At 80 °C, the retention rates were: FGOS / Zein@Ap (96.63%) > FG / Zein@Ap (85.18%) > Zein@Ap (70.80%) > Ap (68.44%). The low Ap retention in Zein@Ap may be due to the failure of zein to fully wrap Ap due to the thermal unfolding. In comparison, the Ap retention rates in FG / Zein@Ap and FGOS / Zein@Ap were significantly higher, especially in FGOS / Zein@Ap. This improvement was attributed to the reduction in hydrophobic attraction, which prevented the collision and aggregation of nanoparticles. In addition, the more compact structure enhanced the stability under high temperature conditions, and FGOS effectively reduced the aggregation of zein nanoparticles and Ap leakage.
[0144] Thermal degradation kinetics:
[0145] The thermal degradation kinetics of Ap of different nanoparticles at 80 °C for 10 h were evaluated. Figure 2 According to the first-order reaction kinetics, free Ap has the highest rate constant (K, 0.1991h -1 ) and the shortest half-life (T 1 / 2 ,3.48h), indicating that its stability is relatively low. Although Zein@Ap has poor short-term thermal stability, its rate constant (0.1397h -1 ) and half-life (4.95h) are better than those of free Ap, indicating that the encapsulated Ap is protected after the initial leakage. FG / Zein@Ap(K,0.0778h -1 , T 1 / 2 ,8.91h) and FGOS / Zein@Ap(K,0.0462h -1 , T 1 / 2 ,14.99h) showed stronger stability, among which FGOS / Zein@Ap provided the strongest protection.
[0146] Photodegradation kinetics:
[0147] The photostability of nanoparticles encapsulated with Ap was investigated. Figure 2 The reaction constant is Ap(0.2782h -1 )>Zein@Ap(0.1552h -1 )>FG / Zein@Ap(0.1135h -1 )>FGOS / Zein@Ap(0.0710h -1 ), and their half-lives were 2.49h, 4.46h, 6.11h, and 9.76h, respectively. This indicates that the photostability of free Ap is poor, while the encapsulation of zein improves its photostability. The FG and FGOS coatings further protected Ap by shielding UV radiation and oxidation, indicating that the introduction of FG and FGOS is beneficial to improve photostability. It is worth noting that FGOS enhances the photostability of FGOS / Zein@Ap compared with FG / Zein@Ap.
[0148] Ionic Strength Stability:
[0149] The ionic strength stability of the nanoparticles was investigated. Figure 2 Zein@Ap nanoparticles were sensitive to NaCl concentration, and the particle size increased dramatically to 582.06±14.36nm at 20mM NaCl. The zeta potential decreased with increasing NaCl concentration, indicating that the anionic salt neutralized the positive charge on the Zein@Ap surface, reduced the electrostatic repulsion, and promoted aggregation. In contrast, FG / Zein@Ap was less affected, but at 40mM NaCl, the particle size increased to 537.36±3.32nm and the zeta potential decreased, which may cause bridging flocculation in a high ionic environment. FGOS / Zein@Ap maintained the particle size below 500nm in the range of 0-50mM NaCl. Despite the significant decrease in zeta potential under 40 and 50mM NaCl conditions, FGOS still maintained a high negative charge, preventing aggregation and mitigating the effect of ionic strength. FGOS enhanced the tolerance and stability of the nanoparticles under ionic conditions.
[0150] Storage stability:
[0151] Storage stability was evaluated at room temperature ( Figure 2JL). The particle size of Zein@Ap increased from 102.63±0.55nm to 351.1±31.18nm within 30d, and precipitation occurred on the 20th day. In contrast, the particle sizes of FG / Zein@Ap and FGOS / Zein@Ap remained stable within 25d, but the particle size and precipitation of FG / Zein@Ap decreased significantly on the 30th day, indicating particle aggregation. The particle size of FGOS / Zein@Ap remained consistent during the 30 days without precipitation. Meanwhile, the free Ap retention rate dropped to 17.99% on the 30th day, indicating poor stability. The Ap retention rate of Zein@Ap decreased, with a final retention rate of 17.04% on the 30th day, mainly due to aggregation and precipitation. FG / Zein@Ap maintained an Ap retention rate of 75.08% on the 25th day, but it dropped to 57.74% on the 30th day. In contrast, FGOS / Zein@Ap maintained a high Ap retention rate of 73.75% on day 30, indicating its superior stability.
[0152] Redispersion stability:
[0153] The redispersion stability of the nanoparticles was evaluated ( Figure 2 After redispersion, the particle sizes of F-Zein@Ap and F-FG / Zein@Ap increased significantly, reaching 1589±82.39nm and 927.11±5.71nm, respectively. The redispersed nanoparticles of F-FGOS / Zein@Ap maintained a particle size of 411.71±10.18nm below 500nm, indicating minimal damage during freeze-drying. This is mainly due to the high carboxyl content in FGOS, which increases the absolute surface potential, enhances electrostatic repulsion, reduces aggregation, and allows FGOS / Zein@Ap to be well dispersed in aqueous solution.
[0154] (5) Evaluation of antioxidant activity:
[0155] The effects of FG and FGOS on Zein@Ap nanoparticles were investigated. Figure 6As shown. With the increase of the concentration of Ap, Zein@Ap, FG / Zein@Ap and FGOS / Zein@Ap, their DPPH radical scavenging ability is enhanced. Due to the limited water solubility, the scavenging rate of Ap is only 50.47% at 100 μg / mL. For Zein@Ap, the scavenging activity is 44.34% in this case, which may be due to the fact that zein partially masks the phenolic hydroxyl groups of Ap, limiting the interaction of free radicals. In addition, zein tends to aggregate in aqueous environments, further limiting the scavenging activity of Ap. Due to the improved water solubility and dispersibility, the scavenging activity of FG / Zein@Ap reaches 56.14%. It is worth noting that FGOS / Zein@Ap has a scavenging activity of 66.98%, which is due to its small particle size, which increases the contact surface area and enhances the interaction between Ap and free radicals.
[0156] The effects of FG and FGOS on ABTS scavenging activity were compared. As the concentrations of Ap, Zein@Ap, FG / Zein@Ap, and FGOS / Zein@Ap increased, their ABTS free radical scavenging abilities were the same as DPPH. FGOS / Zein@Ap showed strong ABTS scavenging abilities in the range of 0 to 100 μg / mL, which was superior to the other groups. At 100 μg / mL, the scavenging rates of FGOS / Zein@Ap (71.91%) > FG / Zein@Ap (64.22%) > Ap (56.61%) > Zein@Ap (55.71%) were the highest. The smaller size and more hydrophilic nature of FGOS / Zein@Ap enhanced the interaction with free radicals, indicating the advantages of FGOS in the delivery system.
[0157] (6) In vitro simulation of gastrointestinal digestion
[0158] The behavior of nanoparticles in the gastrointestinal tract affects the bioactivity of their encapsulated materials. The release of Ap, Zein@Ap, FG / Zein@Ap, and FGOS / Zein@Ap nanoparticles in the stomach and intestine (SGF and SIF) was studied. Figure 3As shown in Figure A, the free Ap release in SGF was 4.46% after 2 h, which was due to its poor solubility under acidic conditions, resulting in precipitation and degradation. In contrast, the free Ap release in SIF reached 15.21% at 240 min, which was due to the weak alkaline environment that improved its solubility and allowed some of the precipitated Ap to be redissolved. In SGF, the Ap encapsulated in the three nanoparticles showed an initial rapid release within the first 30 min, followed by a slow release until 120 min, and then a more stable release throughout the SIF stage. After 30 min, the Ap release from Zein@Ap was 29.73%, while that from FG / Zein@Ap and FGOS / Zein@Ap was 16.59% and 13.11%, respectively, which may be due to the inhibition of pepsin hydrolysis of zein by FGOS and FG. After 2 h of gastric digestion, the Ap release from Zein@Ap was 35.02%, while that from FG / Zein@Ap and FGOS / Zein@Ap was 28.99% and 25.12%, respectively. Figure 3 As shown in Figure BC, the particle size of Zein@Ap increased from 102.6±0.55nm to 1260.3±136.14nm, and aggregation was observed in the TEM image. The particle size of FG / Zein@Ap increased from 291.8±9.63nm to 431.6±32.35nm, and the particle size of FGOS / Zein@Ap increased from 110.5±0.96nm to 280.8±16.13nm, but there was no obvious aggregation. This indicates that the stability of FG / Zein@Ap and FGOS / Zein@Ap is enhanced, among which FGOS provides the best protection.
[0159] In the early stage of SIF (120-150min), Ap release increased because the nanoparticles were broken down by pancreatic enzymes and the higher pH enhanced the solubility of Ap. At 150min, the Ap release of Zein@Ap, FG / Zein@Ap and FGOS / Zein@Ap reached 52.43%, 44.43% and 38.19%, respectively, among which Zein@Ap had the highest Ap release (17.41%), followed by FG / Zein@Ap (15.44%) and FGOS / Zein@Ap (13.07%). This trend is consistent with the study that polysaccharide-protein interactions form denser nanoparticles, which enhances stability during initial intestinal digestion. At the late stage of SIF (240 min), the Ap release further increased, reaching 63.45% for Zein@Ap, 54.21% for FG / Zein@Ap, and 48.87% for FGOS / Zein@Ap, indicating that Zein@Ap was most sensitive to bile salts that emulsified and dissolved Ap, while the particle sizes of Zein@Ap, FG / Zein@Ap, and FGOS / Zein@Ap decreased to 134.5±5.91, 125.1±19.75, and 130.8±6.52 nm, respectively. TEM images confirmed that the FG / Zein@Ap and FGOS / Zein@Ap nanoparticles were uniform, spherical, and well dispersed, while Zein@Ap exhibited adhesion and aggregation due to the hydrolysis of zein by proteases and subsequent reassembly into micelle-like structures by bile salts. Overall, FG / Zein@Ap and FGOS / Zein@Ap exhibited better stability and sustained Ap release, among which FGOS / Zein@Ap showed the best performance.
[0160] (7) Bioaccessibility and bioavailability
[0161] Bioaccessibility:
[0162] The bioaccessibility of various nanoparticles to Ap was evaluated by simulating gastrointestinal digestion in vitro. The bioaccessibility of FGOS / Zein@Ap was the highest (83.31%), significantly better than free Ap (15.93%), Zein@Ap (63.77%), and FG / Zein@Ap (74.74%) ( Figure 3 (D). Encapsulation significantly improved the bioaccessibility of Ap, as free Ap had low bioaccessibility due to poor solubility, leading to precipitation during digestion. The improvement in bioaccessibility of FG and FGOS may be attributed to encapsulation, which not only prevents Ap from degradation under harsh gastrointestinal conditions but also enhances its solubility in the intestinal environment. The good bioaccessibility of FGOS may be due to its more stable and uniform encapsulation properties, which further improves solubility and resistance to gastrointestinal degradation.
[0163] Bioavailability:
[0164] Evaluation of the cytotoxicity of free Ap and various digested nanoparticles ( Figure 3 After 4 h, all digested samples showed good biocompatibility, and the cell survival rate exceeded 90% in the range of 0-60 μg / mL Ap concentration. On this basis, nanoparticles with an Ap concentration of 60 μg / mL were selected for subsequent experiments. When the TEER value of each well exceeded 500 Ω·cm on the 25th day of the Caco-2 cell monolayer model study, the TEER value of each well exceeded 500 Ω·cm 2 Then the cell uptake experiment was carried out (Table 1). After 4 hours of incubation, the cell uptake of Ap was:
[0165] FGOS / Zein@Ap(44.62±2.58%)>FG / Zein@Ap(34.35±2.41%)>Zein@Ap(26.98±1.72%)>Ap(7.54±1.89%), among which FGOS / Zein@Ap showed the most significant improvement ( Figure 3 (I). Free Ap forms micellar particles under the action of bile salts, but its instability leads to low cellular uptake. In contrast, nanoparticles, especially FGOS / Zein@Ap, significantly enhance intracellular Ap uptake due to their smaller size, superior stability and efficient endocytosis.
[0166] The transmembrane transport results further confirmed the superiority of FGOS / Zein@Ap. After 4 h, the transport efficiency into BL was:
[0167] FGOS / Zein@Ap (34.19±0.94%)>FG / Zein@Ap (26.83±0.99%)>Zein@Ap (20.98±0.13%)>Ap (3.53±0.82%). like Figure 3 As shown in Figure J, all delivery systems exhibited time-dependent transport efficiency, while free Ap showed the least change over time. These findings highlight that FGOS / Zein@Ap is the most effective system for promoting cellular uptake and transport of Ap after digestion, emphasizing the key role of FGOS in improving delivery efficiency.
[0168] Figure 3Figure K shows the effect of FG and FGOS on the bioavailability of Ap in cells. Encapsulation significantly improved the bioavailability of Ap compared to free Ap, with Zein@Ap, FG / Zein@Ap, and FGOS / Zein@Ap increasing their bioavailability by 14.31, 21.35, and 30.92 times, respectively. This improvement was due to enhanced stability, reduced degradation, and increased solubility and absorption during digestion. Among the tested nanoparticles, FGOS / Zein@Ap showed the most significant enhancement in bioavailability, outperforming Zein@Ap and FG / Zein@Ap. FGOS is a low molecular weight oligosaccharide with excellent antioxidant activity, which has the effect of stabilizing the delivery system and overcoming the solubility challenges of poorly soluble compounds.
[0169] Table 1 shows the TEER values of Caco-2 cell monolayers on day 25 before and after in vitro permeation studies
[0170] sample <![CDATA[TEER(Ω / cm 2 )]]> Before the test Test after 4 hours Blank digestion fluid 551±6 517±15 Ap 543±10 516±17 Zein@Ap 547±10 521±20 FG / Zein@Ap 553±11 517±21 FGOS / Zein@Ap 558±9 530±22
[0171] (8) Molecular docking
[0172] Molecular docking:
[0173] Molecular docking of Zein-Ap revealed the best model, including the docking process, binding mode, energy, and interaction with the amino acid residues of zein ( Figure 4 ). The ΔG values (ΔG = -6.7 < -5.0) showed strong interactions. Ap interacts with eight key zein residues through hydrogen bonds (GLN62, PRO30), hydrophobic interactions (LEU70, TYR35, ALA34, ILE3, PRO30), and unfavorable receptor-receptor interactions (PHE27) (Table 2). In addition to these direct interactions, van der Waals interactions with surrounding residues were also observed. Ap binds primarily in the pocket between the α-helices of zein rich in hydrophobic amino acids.
[0174] The ΔG between Zein-FG was -5.3 kcal / mol, while that between Zein-FGOS was -6.3 kcal / mol, indicating that the binding mode of the two was more favorable. FG interacted with 10 key amino acid residues of zein through hydrogen bonds (GLN127, THR137, GLN67, ALA135, HIS75 and PRO71), hydrophobic interactions (ALA72, ILE64, VAL139 and HIS131) and unfavorable donor-donor interactions (HIS131). FGOS interacted with 9 key amino acid residues of zein. GLN90, GLN97, ASN152, ARG208, PHE219, GLN211 and GLN153 participated in hydrogen bonds, TYR84 participated in electrostatic interactions, PRO93 participated in hydrophobic interactions, and ARG208 also showed unfavorable donor-donor interactions. Compared with FG, FGOS has more hydrogen bonds and additional electrostatic interactions with TYR84, resulting in a stronger interaction between FGOS and zein, which is attributed to the presence of more hydroxyl groups and additional carboxyl groups in FGOS (Table 2).
[0175] Table 2 shows the binding modes and interactions between zein and Ap, FG or FGOS
[0176]
[0177]
[0178] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A composite material for delivering apigenin containing linseed gum oligosaccharides, characterized in that: The invention comprises nanoparticles formed by zein, wherein apigenin is contained in the nanoparticles and flaxseed gum oligosaccharide is coated on the surface of the nanoparticles.
2. The apigenin delivery composite material containing linseed gum oligosaccharides according to claim 1, characterized in that: The mass ratio of the nanoparticles formed by the zein to apigenin is (15-25):1, and the mass ratio of the nanoparticles to flaxseed gum oligosaccharides is (0.5-4):1; Preferably, the average molecular weight of flaxseed gum oligosaccharides is 1000-1800Da; Preferably, the apigenin delivery composite material containing flaxseed gum oligosaccharides is solid particles or an aqueous solution; Preferably, the particle size of the nanoparticles is less than 150 nm.
3. A method for preparing the apigenin delivery composite material containing linseed gum oligosaccharides according to claim 1 or 2, characterized in that: The antisolvent precipitation method is used to form nanoparticles, including: The alcohol solution of zein is mixed with apigenin to obtain a mixed alcohol solution; The flaxseed gum oligosaccharide aqueous solution and the mixed alcohol solution are mixed, and the alcohol solvent is removed.
4. The preparation method according to claim 3, characterized in that: During the preparation process, the mass ratio of zein to apigenin is controlled to be (15-25):1, and the mass ratio of zein to flaxseed gum oligosaccharide is controlled to be (0.5-4):
1.
5. The preparation method according to claim 4, characterized in that: The preparation process of the mixed alcohol solution includes: mixing zein and an alcohol solvent to make the concentration of zein be 8 mg / mL-12 mg / mL, then mixing with apigenin, adjusting the pH value to 3.8-4.2, and stirring for 2h-7h.
6. The preparation method according to claim 5, characterized in that: The alcohol solvent is an ethanol solution with a volume fraction of 75%-85%; And / or, the pH value is adjusted to 3.8-4.2 using a hydrochloric acid solution with a concentration of 0.05-0.20 mol / L.
7. The preparation method according to claim 4, characterized in that: The preparation process of the flaxseed gum oligosaccharide aqueous solution comprises: mixing flaxseed gum oligosaccharide and water, and adjusting the pH value to 3.8-4.2; And / or, in the aqueous solution of flaxseed gum oligosaccharide, the concentration of flaxseed gum oligosaccharide is 0.625 mg / mL-5 mg / mL.
8. The preparation method according to claim 4 or 7, characterized in that: The mixed alcohol solution is added to the flaxseed gum oligosaccharide aqueous solution, mixed and stirred for 0.5h-3h, the alcohol solvent is evaporated to remove, and then mixed with an aqueous solution with a pH value of 3.8-4.
2.
9. The preparation method according to claim 8, characterized in that: Also includes: After mixing with an aqueous solution having a pH value of 3.8-4.2, freeze drying is performed to obtain a solid granular material.
10. Use of the apigenin delivery composite material containing flaxseed gum oligosaccharides according to any one of claims 1 to 2 or the apigenin delivery composite material containing flaxseed gum oligosaccharides prepared by the preparation method according to any one of claims 3 to 9 in the preparation of apigenin products.